Effect of Muscle Unloading, Reloading and Exercise on Inflammation during a Head-down Bed Rest - Mutin-Carnino, M.; Carnino, A.; Roffino, S.; Chopard, A. (International Journal of Sports Medicine, 2014)
Muscles are affected by unloading during head-down bed rests and by reloading through normal reambulation. This study investigated the effects of a 60 days head-down long-term bed rest with or without predefined exercise countermeasures on the development of an inflammatory reaction.Blood samples were taken before, during and after bed rest in control and exercise groups of women. They were assayed for soluble ICAM-1, VCAM-1, E- and L-selectin, IL1β, IL6, TNFα and CRP as markers of inflammation with ELISA.Head-down long-term bed rest induced plasma volume variations which had an impact on the concentrations of the inflammatory factors and led to data corrections for a reliable analysis of the results. None of the marker of inflammation, except IL6 in control group, showed a significant change from baseline during bed rest. The main results were obtained during recovery. VCAM-1 increased in all groups, ICAM-1, in the control group, and L-selectin, in the exercise group. Peaks of IL6 and CRP were observed on day 59 of bed rest for IL6 and on day 2 of recovery for CRP in the control group. Exercise during bed rest prevented the augmentation of IL6, CRP and ICAM-1. These results might suggest a shift towards pro-inflammatory conditions, prevented in part by exercises.
Keywords: modified muscle use; rehabilitation methods; systemic markers of inflammation; microgravity conditions